(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article briefly provides information about the Far Eastern species of linden (Tilia L.) growing in the collection of the Scientific Research Institute Botanical Garden. E. Gareeva NAS KR.